Distribusi Ukuran Granul dari Tepung Singkong dengan Tepung Tapioka sebagai Pengikat pada Rotary Drum Granulator - Dian Purnami Handayani; Wahyudi Budi Sediawan; Daniel Timotius; Mitha Puspitasari (Eksergi, 2023)
Granulation is a process of monoparticle attachment with a particular mechanism to form a bigger and compact particle which is called granule. Granulation application has been used on many industries like pharmacy and agriculture industries. Research about granulation has been done continuously to get predictive models for various cases. The model which is only applicable to the specific material used in this research is expected to be useful to optimize the perfomances of the granulator in the industries. This research aims to develop the kinetics model of granule size distribution of cassava flour and its connection to granulation time by varying the mass of tapioca starch as the binder in rotary drum granulator. 2 grams of Cassava flour and tapioca starch were mixed in the rotary drum granulator and then water was sprayed during the granulation process. The duration of granulation were 5, 10, 15, 20, and 25 minutes. The variations of mass of the binder used in this research were 1, 1,5, and 2 gram. The granules were dried in the oven at 80Â°C until 30 minutes, and afterwards the granules were screened through various screen layers with different mesh size. The results of this research show that binder mass variations do not influence the layering rate of granule, and the increase of binder mass will decrease the birth rate.